Corruption KPK Threatened to Not Be Captured Board Of Directors of State-Owned Enterprises - A. Junaedi Karso (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The Law on State-Owned Enterprises (BUMN) by the Indonesian House of Representatives on February 4, 2025 has been ratified, and then signed by President Prabowo Subianto on February 24, 2025, destroying the concept of who the state administrators are as regulated in Law Number 28 of 1999 concerning the Implementation of a Clean State Free from Corruption, Collusion, and Nepotism.Law No. 1 of 2025 concerning BUMN, places the directors, commissioners, and supervisors of the state-owned company not as state administrators. This means that the Corruption Eradication Commission or KPK can no longer handle law enforcement in BUMN if corruption occurs, except for the Police, Prosecutor's Office and BPK (supervision), as stated in Article 3X of Law No. 1 of 2025, which states that: